SIGNIFICANT WAVE HEIGHT FORECASTING BY USING TYPE-2 FUZZY - 'ABDUL HASHIM, MAYMUNAH (2013)
ignificant wave height parameter plays an important role in ocean and coastal activities. However, the forecasting process of this parameter involved with uncertainty due to the nature of data. In past decades, fuzzy logic was introduced by Zadeh that enables a computer system to reason with uncertainty. This theory had widely applied in many applications, including wave parameter forecasting. Currently, wave height forecasting techniques were focusing on using Type-1 fuzzy method. This technique has a limitation in handling and minimizing uncertainties 'which affect the accuracy ofthe forecasting result. Therefore, this research is aimed to propose a method on forecasting significant wave height by using Type-2 fuzzy.